Hard town - Plantinga, Adam (Kurt Argento, 2025)
"When a plea for help sends retired Detroit cop Kurt Argento to the small desert town of Fenton, Arizona things immediately don't appear to be as they seem, and he finds himself unraveling secrets that want to stay hidden and questioning his own moral compass. After having survived a deadly prison break, ex-Detroit cop Kurt Argento is ready for some quiet. Still working through his grief over the passing of his wife, Argento finds himself house-sitting for a friend with his loyal companion, Hudson, a Chow Chow-Shepard mix. It's a simple life, picking up odd jobs here and there, but it's one that Argento is content to live. Then Kristin Reed shows up with her young son, Ethan, and begs Argento to help find her missing husband... and Argento tells her he'd just be in the way. He's no investigator, not anymore. He's a handyman who fixes fences. But he's not one to ignore his gut feeling when something is wrong. After an attempt to talk with Kristin more in the next town over, just to find her and her son missing as well, Argento starts to notice that Fenton, Arizona is more than meets the eye. First there's the large, overly equipped public safety team complete with specialized tactics and sophisticated weaponry. Then there's the unusual financial boosting of failing small businesses by the U.S. government. And finally, there's one man with no name who seems to have control over this town in an unprecedented way. Argento finds himself unraveling not just the truth behind the disappearance of a family, but a conspiracy that's taken a whole town to cover up. But Fenton, Arizona is going to push him further than he's ever had to go. And along the way, he may just lose a part of himself as well. Because justice isn't as black and white as Argento would like to believe"--